ANALISIS PENGARUH PEMASARAN DIGITAL TERHADAP PENJUALAN PRODUK UMKM FASHION (STUDI KASUS : MALESSA FASHION) - Arista Juni Rahmawati; Yuni Prihadi Utomo (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of digital marketing on product sales in fashion MSMEs, with a case study focusing on Malessa Fashion. In the midst of the digitalization era, MSMEs are required to adapt to technological changes, one of which is through the implementation of digital marketing strategies. In this study, a qualitative approach was used with a semi-structured interview method involving business owners as the main source of information. The results of the study show that Malessa Fashion utilizes three main digital platforms, namely Instagram, Facebook, and WhatsApp Business, as a means of promotion, communication, and distribution of information about products. The marketing strategy implemented has proven effective in increasing sales and expanding market reach. The data shows a significant increase in turnover and net profit after the digital marketing strategy was implemented consistently. However, there are still several aspects that need to be improved, especially in terms of the quality of visual content, consistent uploads, and optimization of interaction features on each platform. Therefore, this study recommends improving the quality of visuals and digital interactions to strengthen consumer loyalty and increase business competitiveness.